IGF-1 Facilitates Cartilage Reconstruction by Regulating PI3K/AKT, MAPK, and NF-kB Signaling in Rabbit Osteoarthritis - Hossain MA (Dove Medical Press, 2021)
Mohammad Amjad Hossain,1 Aravinthan Adithan,1 Md Jahangir Alam,1 Spandana Rajendra Kopalli,2 Bumseok Kim,1 Chang-Won Kang,1 Ki-Chul Hwang,3 Jong-Hoon Kim1 1College of Veterinary Medicine, Biosafety Research Institute, Chonbuk National University, Iksan-city, Jeollabuk-Do, Republic of Korea; 2Department of Integrative Bioscience and Biotechnology, Sejong University, Gwangjin-gu, Seoul, 05006, Republic of Korea; 3Institute for Bio-Medical Convergence, College of Medicine, Catholic Kwandong University, Gangneung-si, Gangwon-do, Republic of KoreaCorrespondence: Jong-Hoon KimCollege of Veterinary Medicine, Biosafety Research Institute, Chonbuk National University, 79 Gobong-ro, Iksan-city, Jeollabuk-Do, 54596, Republic of KoreaEmail jhkim1@jbnu.ac.krPurpose: The pathogenesis of osteoarthritis (OA) is characterized by joint degeneration. The pro-inflammatory cytokine interleukin (IL)-1β plays a vital role in the pathogenesis of OA by stimulation of specific signaling pathways like NF-κB, PI3K/Akt, and MAPKs pathways. The catabolic role of growth factors in the OA may be inhibited cytokine-activated pathogen. The purpose of this study was to investigate the potential effects of insulin-like growth factor-1 (IGF-1) on IL-1β-induced apoptosis in rabbit chondrocytes in vitro and in an in vivo rabbit knee OA model.Methods: In the present study, the OA developed in chondrocyte with the treatment of IL-1β and articular cartilage ruptures by removal of cartilage from the rabbit knee femoral condyle. After IGF-1 treatment, immunohistochemistry and qRT-PCR were identified OA expression with changes in MMPs (matrix metalloproteinases). The production of ROS (intracellular reactive oxygen species) in the OA was detected by flow cytometry. Further, the disease progression was microscopically investigated and pathophysiological changes were analyzed using histology. The NF-κB, PI3K/Akt and P38 (MAPK) specific pathways that are associated with disease progression were also checked using the Western blot technique.Results: The expression of MMPs and various apoptotic markers are down-regulated following administration of IGF-1 in a dose-dependent fashion while significantly up-regulation of TIMP-1. The results showed that higher levels of ROS were observed upon treatment of chondrocytes and chondral OA with IL-1β. Collectively, our results indicated that IGF-1 protected NF-κB pathway by suppression of PI3K/Akt and MAPKs specific pathways. Furthermore, the macroscopic and pathological investigation showed that it has a chondroprotective effect by the formation of hyaline cartilage.Conclusion: Our results indicate a protective effect of IGF-1 against OA pathogenesis by inhibition of NF-κB signaling via regulation of the MAPK and PI3K/Akt signaling pathways and prevention of apoptosis by suppression of ROS production.Keywords: insulin-like growth factor-1, chondrocyte, cartilage development, osteoarthritis, rabbit